Merit System in Administration and Supervising Staff Career Promotion in Universitas Brawijaya - Endah Setyowati (Wacana Journal of Social and Humanity Studies, 2020)
Implementation of a new structure of organization and working procedures in Universitas Brawijaya brings a significant change. Some administration and supervising staff lost their positions. As a result, the university analyzes to select a suitable career promotion system to hire the best man for the best position. The merit-based system becomes a selected strategy as it allows Universitas Brawijaya to appoint individuals with the right competence. The objectives of this study were to analyze the implementation of a merit-based system in administration and supervising staff promotion in Universitas Brawijaya and HR strategy the university applied. The finding showed that the university has implemented a merit-based system for administration and supervising staff promotion. All eligible candidates have equal opportunity, information about the selection process was accessible for everyone (transparent), and the university designed a passing grade for the promotion process. However, administration (lack of competence) and psychological (non-conducive atmosphere for implementation of the merit-based system) aspects became issues the university should encounter. Thus, Universitas Brawijaya should have adequate planning to make sure that the merit-based system is the only system used for administration and supervising staff career promotion.